The general equation for translating is expressed as:
g(x) = f(x - a) + b
where a = horizontal shift
b = vertical shift
Given the function
On comparing with the standard equation, we can see that
b = -4
which shows that the translation requires a vertical shift of four units (downwards)
also
x-a = x+3
On comparing
a = -3
this shows that the translation requires a horizontal shift of 3 units (towards the left being negative)
Hence the student is correct. The x-3 in 1/x+3 implies a leftwrad shift of 3units and a constant -4 implies downward shift of 4units